Experimental disturbance and productivity gradients drive community diversity in aquatic mesocosms - Jacob D. Hart; David G. Jenkins (Ecology and Evolution, 2023)
Abstract Combined effects of disturbance and productivity on ecological diversity have been considered for decades as the dynamic equilibrium model (DEM) but are rarely tested together. Instead, most studies focus on either the intermediate disturbance hypothesis or sometimes the intermediate productivity hypothesis. In addition, most analyses of disturbance and productivity effects have relied on nonexperimental patterns, limited sample sizes, inaccurate proxies for productivity, and/or simple measures of diversity. The DEM operates at regional and local scales; here, we conducted a year‐long experiment at local scales using submersed aquatic vegetation in outdoor mesocosms with a factorial combination of physical disturbance and productivity treatments. We evaluated diversity in several ways, directly measured productivity, and compared alternative hypotheses using model selection. The DEM was supported for effective diversity; both productivity and disturbance effects were clear, though productivity effects were stronger. Other diversity measures for the simple communities in the mesocosms did not clearly reflect treatments. The DEM is a valuable general framework for understanding disturbance and productivity effects on ecological systems and is made more general by minor conceptual adjustments here.